Korelasi Layanan Internet dengan Akses Layanan Perpustakaan di Kalangan Mahasiswa dalam Membantu Manajemen Perpustakaan (Studi Kasus di Perpustakaan IAIN Kediri) - Puspoko Ponco Ratno; Ayu Tahta Nur Aida; Laily Nur Qomariyah (Journal of Islamic Education Management, 2021)
This study has a background to determine the correlation between internet services and library access services at IAIN Kediri, so that the results can be used to facilitate librarians in arranging the priority needs of library service users, especially students. This research uses quantitative research method by collecting data through a questionnaire distributed to 300 students. The result of the questionnaire is then analyzed to gain the correlation value to find relationships between variables followed by looking for regression values to determine the influence of one variable on another. To determine the value of validity and reliability, the Pearson Correlation Product Moment formula and Alpha-Cronbach formula are used. Based on the results of the data analysis technique using simple linear regression, between the independent (internet services) and the dependent variable (services in the library) has a correlation value (R2) of 25.5% which means that there is a positive correlation (interrelated between one variable and one variable). other). Briefly, it can be concluded that internet services have a correlation with access to library services and an important role in supporting student learning activities. Accordingly, librarians are strongly expected to carry out management especially in terms of library service facilities and infrastructure at IAIN Kediri.